2019
DOI: 10.3390/polym11040743
|View full text |Cite
|
Sign up to set email alerts
|

Pluronic F127-Folate Coated Super Paramagenic Iron Oxide Nanoparticles as Contrast Agent for Cancer Diagnosis in Magnetic Resonance Imaging

Abstract: Contrast agents have been widely used in medicine to enhance contrast in magnetic resonance imaging (MRI). Among them, super paramagnetic iron oxide nanoparticles (SPION) have been reported to have low risk in clinical use. In our study, F127-Folate coated SPION was fabricated in order to efficiently target tumors and provide imaging contrast in MRI. SPION alone have an average core size of 15 nm. After stabilizing with Pluronic F127, the nanoparticles reached a hydrodynamic size of 180 nm and dispersed well i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(32 citation statements)
references
References 28 publications
0
32
0
Order By: Relevance
“…Esterification occurs in the carboxylic acid portion of secondary carbon, which is more reactive in folic acid. In addition, the CDI of the primary carbon carboxylic acid portion of folic acid is removed by treating the strong acid (HCl) in the precipitation process after the reaction [ 31 , 32 ]. The synthesis of AF was confirmed by 1 H NMR.…”
Section: Resultsmentioning
confidence: 99%
“…Esterification occurs in the carboxylic acid portion of secondary carbon, which is more reactive in folic acid. In addition, the CDI of the primary carbon carboxylic acid portion of folic acid is removed by treating the strong acid (HCl) in the precipitation process after the reaction [ 31 , 32 ]. The synthesis of AF was confirmed by 1 H NMR.…”
Section: Resultsmentioning
confidence: 99%
“…Oleic acid, magnetic nanoparticles, Pluronic polymers and folic acid are usual water dispersible nanoparticle-based formulation to increase the water dispersibility, targeting ability and biosafety. Recently, Hieu et al 22 reported a similar system for cancer diagnosis. First, magnetic Fe 3 O 4 nanoparticles were prepared by the co-precipitation method and then stabilized by F127-FA.…”
Section: Discussionmentioning
confidence: 99%
“…It was confirmed that these nanoparticles have an active targeting ability to folic acid receptors in vivo and are useful for imaging cancer tissues. [ 391 ] Enhancement of anti-cancer activity Polysorbate 20 Silver Around 5 nm HEK293T cells, MDA-MB-231 cells Silver nanoparticles coated with polysorbate 80 and albumin or hemoglobin were prepared. Prepared nanoparticles exhibited increased biocompatibility and selective toxicity to cancer cells.…”
Section: Application Of Surfactant-coated Nanoparticles In Nanomedicinementioning
confidence: 99%